U.S.and ex-USSRRelationsDuring theCold WarCasestudy:TheCubanMissileCrisis - Souiah Zohir-AoudjOmarELFaroukK, hirani ElHosseyn (My University, 2019)
Abstract: ThepresentpaperexplorestherelationshipbetweenthetwosuperpowerstheUnitedStatesofAmericaandtheSovietUnionduringtheColdwartheUSandtheSovietUnion progressivelybuilt uptheir ownzonesof influence,dividingtheworld intotwoopposingcamps.TheColdWarwasthereforenotcompletelyastrugglebetweentheUSandtheUSSRbutaglobalconflictthataffectedmanycountries,particularlyintheEuropeancontinent,Asia,andSouthAmericawheretheconflictreacheditsclimaxexactlyinCuba(CubanMissileCrisis),because,in1959,CubabecameacommunistcountryandtheSovietssecretlydeployedmissilesthere.TheU.S.PresidentKennedywasscaredtheSovietUnionwouldattacktheUnitedStates.HeexpectedablockadeonCubawouldobligetheSovietUniontoremoveitsmissiles,whichunfortunatelydidnothappen.Forahostageof13days,nuclearwarseemedpossiblebutfortunately,throughtheeffortsofU.Nthemissilecrisishadbeensolvedfollowedbyagreementsinitsaftermath.
Keywords: Keywords:US,USSR,ColdWar,CubanMissileCrisis,UN.